Performance study of rotated QAM signals over Interference and fading channels - Khui, Kenneth Yi Cheng (Nanyang Technological University, 2024)
Quadrature Amplitude Modulation (QAM) is a widely utilized fundamental digital modulation technique used in modern communication systems. This project will delve into both conventional and rotated QAM, where the constellation of the latter is pivoted around its origin by a specific angle. Using MATLAB simulations, this project will evaluate the Bit Error Rate (BER) performance against Signal-to-Noise Ratio (SNR) across two fading channels, namely Rayleigh and Rician fading channels, along with Additive White Gaussian Noise (AWGN). The simulation results of both the conventional QAM and rotated QAM will then be compared and reviewed against each other across AWGN and various fading channels.